Betulinic acid induces apoptosis and suppresses metastasis in hepatocellular carcinoma cell lines in vitro and in vivo. Issue 1 (12th November 2018) - Wang, Wei; Wang, Yang; Liu, Mingxing; Zhang, Yifan; Yang, Tao; Li, Dongsheng; Huang, Yinpeng; Li, Qing; Bai, Guang; Shi, Linlin
Abstract: Hepatocellular carcinoma (HCC) is a high incidence and mortality malignant tumour globally. Betulinic acid (BA) is a pentacyclic triterpenoid with potential pro‐apoptotic activities which widely found in many plants. In this study, we determined the effects of BA on proliferation, apoptosis, invasion, and metastasis in HCC cell lines and on tumour growth and pulmonary metastasis in mice. The results suggested that BA could inhibit cell viability and proliferation of HCC cell lines including HepG2, LM3, and MHCC97H. In addition, BA induced apoptosis of HepG2 cells characterised condensed nuclei and nuclear fragmentation. Moreover, western blot analysis showed that BA‐induced apoptosis associated with increasing of pro‐apoptotic protein Bax and cleaved caspase‐3 and decreasing of anti‐apoptotic protein Bcl‐2. Meanwhile, BA also reduced the reactive oxygen species (ROS) level. Furthermore, BA also significantly inhibited HCC growth in vivo and blocked pulmonary metastasis of HCC by regulating the metastasis‐related proteins including MMP‐2, MMP‐9, and TIMP2 without obvious toxicity. In all, the present study suggested that BA might be a promising anti‐HCC drug candidate by inhibiting proliferation, inducing apoptosis, and blocking metastasis.